Edge transport and fuelling studies via gas puff modulation in ASDEX Upgrade L-mode plasmas. (1st June 2022) - Schuster, C.U.; Wolfrum, E.; Fable, E.; Fischer, R.; Griener, M.; Tal, B.; Angioni, C.; Eich, T.; Manz, P.; Stroth, U.; the ASDEX Upgrade Team
Abstract: Gas puff modulation experiments are performed at ASDEX Upgrade in L-mode plasmas. We model the discharge with the ASTRA transport code in order to determine transport coefficients outside of a normalized radius of ρ pol = 0.95. The experimental data is consistent with a range of particle diffusivities and pinch velocities of the order of D = (0.20 ± 0.13) m 2 s −1 and v = (−1 ± 2) m s −1, respectively. The electron temperature response caused by the gas modulation permits to estimate also that heat diffusivity χ e increases almost linearly when collisionality rises due to fuelling. The fuelling particle flux is amplified by recycling, overcompensating losses.